2007
DOI: 10.1074/jbc.m701083200
|View full text |Cite
|
Sign up to set email alerts
|

CatSperβ, a Novel Transmembrane Protein in the CatSper Channel Complex

Abstract: Four CatSper ion channel subunit genes (CatSpers 1-4) are required for sperm cell hyperactivation and male fertility. The four proteins assemble (presumably as a tetramer) to form a sperm-specific, alkalinization-activated Ca 2؉ -selective channel. We set out to identify proteins associating with CatSper that might help explain its unique role in spermatozoa. Using a transgenic approach, a CatSper1 complex was purified from mouse testis that contained heat shock protein 70-2, a testisspecific chaperone, and Ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

6
159
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 153 publications
(165 citation statements)
references
References 39 publications
(34 reference statements)
6
159
0
Order By: Relevance
“…This weak voltage dependency is thought to be the result of heterogeneity of the arginine and lysine composition of the putative voltage sensor domains within the CatSper ␣ subunits. The characteristic CatSper current (I CatSper ) is lost in mice lacking any of the CatSper ␣ subunits (CatSper1-4) or the accessory subunit CatSper ␦ and, as previously mentioned, are all infertile due to an inability of CatSper null spermatozoa to hyperactivate resulting in an inability of sperm to pass into the oviduct to reach the egg [9,10,16,21,22,24,[71][72][73][81][82][83].…”
Section: Calcium Channels and Hyperactivationmentioning
confidence: 95%
See 1 more Smart Citation
“…This weak voltage dependency is thought to be the result of heterogeneity of the arginine and lysine composition of the putative voltage sensor domains within the CatSper ␣ subunits. The characteristic CatSper current (I CatSper ) is lost in mice lacking any of the CatSper ␣ subunits (CatSper1-4) or the accessory subunit CatSper ␦ and, as previously mentioned, are all infertile due to an inability of CatSper null spermatozoa to hyperactivate resulting in an inability of sperm to pass into the oviduct to reach the egg [9,10,16,21,22,24,[71][72][73][81][82][83].…”
Section: Calcium Channels and Hyperactivationmentioning
confidence: 95%
“…Three other gene products later identified based on their similarity to CatSper1 also encode ␣ subunits of the complex: CatSper2-4 [6,9,69,70]. Additionally, auxiliary subunits CatSper␤, ␥, and ␦ have been shown to co-localize and associate with the CatSper complex, suggesting that CatSper is a heteromeric ion channel complex of at least 7 different subunits [71][72][73] (Fig. 2).…”
Section: Calcium Channels and Hyperactivationmentioning
confidence: 99%
“…Because mouse CatSper current recorded from epididymal spermatozoa is not sensitive to progesterone (18), we concluded that the sperm nongenomic progesterone receptor is either missing in mice or the mouse CatSper does not respond upon engagement of this receptor. CatSper is expressed in spermatozoa of many species, but orthologs of some CatSper subunits share low identity (50% or less) (28,29), which can explain why regulation of the CatSper channel can differ between species. Although responsiveness of human CatSper to progesterone arises early in sperm development concurrently with the pore of the CatSper channel, this observation does not necessarily mean that CatSper itself serves as the sperm nongenomic progesterone receptor.…”
Section: Discussionmentioning
confidence: 99%
“…So far, however, experimental procedures enabling unbiased and comprehensive access to the environment of membrane proteins have been missing or have just begun to evolve (17)(18)(19)(20)(21)(22)(23)34).…”
Section: Discussionmentioning
confidence: 99%
“…Antibody-based affinity purification (AP) combined with quantitative MS is a target-directed approach, which, theoretically, allows for strong enrichment of both target proteins and more stably associated partners with tight control of specificity and interaction stringency (16). In fact, AP-based proteomics were successfully used for identification of accessory subunits and regulators of various ion-channel proteins (17)(18)(19)(20)(21)(22)(23). Notwithstanding, there remain several sources of error that are aggravated considerably when approaching protein networks such as those comprising nanoenvironments.…”
mentioning
confidence: 99%